Outcomes of OCT imaging-based reoperations in strabismus - Savleen Kaur; Jaspreet Sukhija; Srishti Raj; Shweta Chaurasia; Shubhi Singh M. Optom (BMC Ophthalmology)
Abstract Purpose Reoperations in strabismus are reportedly needed in 20–40% of cases undergoing surgery. The present study investigated the outcomes of reoperations based on preoperative imaging of extraocular muscle insertions, and whether the Anterior Segment Optical Coherence Tomography (ASOCT) was of value. Methods Patients with strabismus requiring reoperation with/without previous surgical records at the Advanced Eye Centre, PGIMER, Chandigarh were recruited. All patients underwent a thorough clinical examination and imaging of extraocular muscle insertions on the Swept Source Anterior Segment Optical Coherence Tomography. The accuracy of measuring muscle insertions with the ASOCT was compared with intraoperative caliper readings. Results Forty-seven muscles (28 patients) were imaged on ASOCT with confirmation intraoperatively during re-operation. The mean age of the patients was 21.6 ± 5.6 years. After looking at the imaging findings, the decision of which muscle to operate on changed in eleven patients (39.2%). The accuracy of ASOCT to measure muscle insertion ± 1 mm was seen in 78.7% (38/47 muscles). The ASOCT could give additional information, such as a slipped muscle and stretched scar in three patients. Conclusions Imaging can be beneficial in achieving successful results in strabismus reoperations with high accuracy. It can be pivotal in surgical planning in reoperations (~ 40%).